2016
DOI: 10.1016/j.ympev.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of C4orf26 in toothless placental mammals

Abstract: Previous studies have reported inactivated copies of six enamel-related genes (AMBN, AMEL, AMTN, ENAM, KLK4, MMP20) and one dentin-related gene (DSPP) in one or more toothless vertebrates and/or vertebrates with enamelless teeth, thereby providing evidence that these genes are enamel or tooth-specific with respect to their critical functions that are maintained by natural selection. Here, we employ available genome sequences for edentulous and enamelless mammals to evaluate the enamel specificity of four genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 86 publications
4
56
0
Order By: Relevance
“…45 Phylogenetic analyses showed the presence of an intact Wdr72 gene in the Chinese pangolin and three types of baleen whales that don't make teeth, and in the aardvark, nine-banded armadillo, Hoffmann's two-toed sloth that make enamel-less teeth. 46 The observation of intact genes in these vertebrates contrasts with genes that are truly specialized for amelogenesis, which become pseudogenized in these species. 9 Recently, WDR72 defects were shown to cause AI with distal renal tubular acidosis (dRTA).…”
Section: Resultsmentioning
confidence: 99%
“…45 Phylogenetic analyses showed the presence of an intact Wdr72 gene in the Chinese pangolin and three types of baleen whales that don't make teeth, and in the aardvark, nine-banded armadillo, Hoffmann's two-toed sloth that make enamel-less teeth. 46 The observation of intact genes in these vertebrates contrasts with genes that are truly specialized for amelogenesis, which become pseudogenized in these species. 9 Recently, WDR72 defects were shown to cause AI with distal renal tubular acidosis (dRTA).…”
Section: Resultsmentioning
confidence: 99%
“…However, MMP20 also appears to be a pseudogene in pygmy sperm whales (Kogia breviceps) and Hoffman's two-toed sloths (Choloepus hoffmanni), which both have teeth without enamel, implying that MMP20 is critical exclusively to enamel production. Springer et al (2015) identified inactivating mutations of a different gene C4orf26, which occurs only in toothless, but not enamel-less taxa. This pattern implies that C4orf26, unlike the other genes mentioned above, is tooth-specific but not enamel-specific; moreover, it reinforces a decoupling between the processes responsible for tooth and enamel production.…”
Section: Molecular Evidencementioning
confidence: 99%
“…was found to contain four fixed non-synonymous substitutions derived in the Antarctic lineages, based on the inferred ancestral state, which resulted in physicochemical changes including a hydrophobic side chain being replaced by a positively charged side chain. The keratin-associated protein encoded by the FAM83H gene is thought to be important for skin development and regulation 52,53 , through regulation of the filamentous state of keratin within cytoskeletal networks in epithelial cells, determining processes such as cell migration and polarization 54,55 . Skin regeneration is thought to be constrained in killer whales whilst inhabiting the cold waters around Antarctica due to the high cost of heat loss, and is thought to underlie rapid round-trip movements to warmer subtropical waters by Antarctic ecotypes 56 .…”
Section: Genome-wide Landscape Of Genetic Diversity and Differentiatimentioning
confidence: 99%